Do neighborhood social processes moderate the etiology of youth conduct problems?. Issue 9 (1st July 2020) - Burt, S. Alexandra; Clark, D. Angus; Pearson, Amber L.; Klump, Kelly L.; Neiderhiser, Jenae M.
Abstract: Background: Prior work has robustly suggested that social processes in the neighborhood (i.e. informal social control, social cohesion, norms) influence child conduct problems (CP) and related outcomes, but has yet to consider how these community-level influences interact with individual-level genetic risk for CP. The current study sought to do just this, evaluating neighborhood-level social processes as etiologic moderators of child CP for the first time. Methods: We made use of two nested samples of child and adolescent twins within the Michigan State University Twin Registry (MSUTR): 5649 families who participated in in the Michigan Twins Project (MTP) and 1013 families who participated in the Twin Study of Behavioral and Emotional Development (TBED-C). The neighborhood social processes of informal social control, social cohesion, and norms were assessed using neighborhood sampling techniques, in which residents of each twin family's neighborhood reported on the social processes in their neighborhood. Standard biometric GxE analyses evaluated the extent to which they moderated the etiology of CP. Results: The 'no moderation' model provided the best fit to the data in nearly all cases, arguing against neighborhood social processes as etiologic moderators of youth CP. Conclusions: The neighborhood social processes evaluated here do not appear to exert their effects on child CP via etiologic moderation. The documented links between neighborhood social processes and child CP are thus likely to reflect a different etiologic process. Possibilities include environmental main effects of neighborhood social processes on child CP, or genotype-environment correlations.